Scope and limitations of information sources for monitoring the right to adequate housing in Argentina - Molinatti, Florencia (2023)
This article proposes to analyze the scope and limitations of the official information sources available in Argentina in the last 22 years for monitoring the exercise of the right to adequate housing, providing a frame of reference for its measurement. First, a compilation of the main indicators recognized as relevant is made, based on the conceptualization of adequate housing on which the New Urban Agenda is based. Subsequently, the main official sources of information produced in the period and the availability of basic information for the calculation of the indicators collected are analyzed. Among the main conclusions, it is highlighted that in Argentina there is the possibility of creating a system of indicators to monitor this right based on the available sources of information, making it possible to cover five of the seven minimum criteria, although not for all the proposed indicators. Likewise, the loss of effectiveness of some traditionally used indicators and the emergence of new dimensions of analysis are highlighted, which demands new surveys to deepen into the complexity and delve on key aspects of the right to adequate housing.